30 anos de DHS: o que andamos pesquisando sobre fecundidade no Brasil - Coutinho, Raquel Zanatta; Barros, Juliana Vasconcelos de Souza; Carvalho, Angelita Alves de (Revista Brasileira de Estudos de População, 2015)
DOI http://dx.doi.org/10.1590/S0102-30982015000000023